(untitled) (Asian Journal of Medical and Biological Research, 2020)
Natural water bodies in Bangladesh are under threat of encroachment due to high population pressure, overexploitation, change of watercourses, and siltation. Therefore, the present study carried out to assess the degree of encroachment of floodplains and its impact on fish biodiversity and the livelihoods of the neighboring fishing communities. The study covered three beels of Naogaon district through remote sensing image interpretation and PRA techniques. The study used three dates remote sensing images and field data which supplemented with the secondary data from diverse origins. Data collected through the recalling method, personal interview with a structured questionnaire and livelihood analysis of fishermen and non-fishermen group living around the beels. The data interpretation showed the water area reduced by 80% from 1981 to 2016 in dry season that converted to boro rice cultivation gradually over time. The type of fishing gears and their use also changed radically over time in all the three beels. The fish catch increased steadily from 1981 and reached its peak in 1996, and then started to fall and continued up to 2016 in all the three beels. The study identified thirty species of SIS and SRS in 1981 that were gradually reduced to 6, 8 and 9 in Digholi, Fatepur and Pakuria beels respectively in 2016. Fish biodiversity reduced as fish-friendly large mesh cotton net replaced by the smaller mesh jagotber jal and monofilament synthetic current jal. Moreover, the annual income of the fishermen family was lower than non- fishermen family in beels areas. The current study clearly identified significant encroachment of floodplains area by agricultural activities between 1981 and 2016 and aquatic biodiversity reduced dramatically and the livelihoods of poor fishermen became vulnerable. Asian J. Med. Biol. Res. June 2020, 6(2): 244-254